Biochemical, Conformational, and Immunogenic Analysis of Soluble Trimeric Forms of Henipavirus Fusion Glycoproteins - Chan, Yee-Peng (American Society for Microbiology, 2012)
The henipaviruses, Hendra virus (HeV) and Nipah virus (NiV), are paramyxoviruses discovered in the mid- to late 1990s that possess a broad host tropism and are known to cause severe and often fatal disease in both humans and animals. HeV and NiV infect cells by a pH-independent membrane fusion mechanism facilitated by their attachment (G) and fusion (F) glycoproteins. Here, several soluble forms of henipavirus F (sF) were engineered and characterized. Recombinant sF was produced by deleting the transmembrane (TM) and cytoplasmic tail (CT) domains and appending a glycosylphosphatidylinositol (GPI) anchor signal sequence followed by GPI-phospholipase D digestion, appending a trimeric coiled-coil (GCNt) domain (sF(GCNt)), or deleting the TM, CT, and fusion peptide domain. These sF glycoproteins were produced as F(0) precursors, and all were apparent stable trimers recognized by NiV-specific antisera. Surprisingly, however, only the GCNt-appended constructs (sF(GCNt)) could elicit cross-reactive henipavirus-neutralizing antibody in mice. In addition, sF(GCNt) constructs could be triggered in vitro by protease cleavage and heat to transition from an apparent prefusion to postfusion conformation, transitioning through an intermediate that could be captured by a peptide corresponding to the C-terminal heptad repeat domain of F. The pre- and postfusion structures of sF(GCNt) and non-GCNt-appended sF could be revealed by electron microscopy and were distinguishable by F-specific monoclonal antibodies. These data suggest that only certain sF constructs could serve as potential subunit vaccine immunogens against henipaviruses and also establish important tools for further structural, functional, and diagnostic studies on these important emerging viruses.